Evaluation of swirling flow phenomenon in direct contact membrane distillation - Moujdin, Iqbal Ahmed; Totah, Husam Saber; Allaf, Ibrahim; Abulkhair, Hani; Fayed, Mohamed (Frontiers in Mechanical Engineering, 2025)
The global water crisis is growing so severe that there is a need for innovative technologies for effective desalination. The utilization of cutting-edge techniques for the treatment of seawater and saline water using membrane distillation (MD) has several advantages that are significant benefits. This study investigates how swirling flow configurations can improve the performance of Direct Contact Membrane Distillation (DCMD) modules. Swirling flow can be used to create turbulence, which lowers temperature polarization (TP) and concentration polarization (CP). This makes it easier for heat and mass to move through the system. An experimental DCMD system has been set up to study the effect of varying permeate flow rates and temperature differences on permeate flux. The results reveal that higher flow rates and temperature differences significantly enhance the overall performance, up to a limit. This study highlights the potential of swirling flow techniques to improve the efficiency and scalability of MD systems in a bid to enhance the desalination or treatment of water.